Implication of BPJS for Private Health Insurance Marketing and Business Competition in Indonesia - Iis Nismawati; Umaruzzaman Umaruzzaman; Erlina Puspitaloka Mahadewi (International Journal of Health and Pharmaceutical (IJHP), 2022)
Social security is a constitutional right owned by citizens that must be fulfilled by the state for its citizens in Indonesia. The growth of companies in Indonesia has increased from year to year. One of the service companies that is developing is an insurance company. Lots of private insurance companies are also growing and developing at this time. However, in the midst of competition from insurance companies, there is a new policy from the government. The government policy is one of the state-owned insurance companies, PT. Askes (Persero) changed its name to BPJS which applies to all people. Currently PT. Askes (Persero) changed to BPJS which serves all Indonesian citizens without any difference. The implementation of BPJS in early year 2014, seems to have had an impact on a number of insurance companies. This mandatory program from the government inevitably affects the competitive landscape of the insurance industry in Indonesia, especially private insurance companies that serve health and other private insurance companies. In the end, competition is expected to become a mechanism capable of creating efficiency that functions as a tool to protect consumers and business actors. This study uses a qualitative method, aiming to analyze the development of BPJS, its developments and implications, especially in the world of healthcare insurance business in Indonesia. From healthy insurance business and competition, it is hoped that efficient, effective, and high-quality production will be achieved. So that the ultimate goal of this research is to highlight what are the things that benefit consumers because they are given the opportunity to have a choice of quality products and can buy at competitive prices which tend to be relatively cheap.